2016
DOI: 10.2134/jeq2016.04.0140
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Emissions from Open‐Lot Cattle Feedyards: A Review

Abstract: Nitrous oxide (N 2 O) emissions from concentrated animal feeding operations, including cattle feedyards, have become an important research topic. However, there are limitations to current measurement techniques, uncertainty in the magnitude of feedyard N 2 O fluxes, and a lack of effective mitigation methods. The objective of this review was to assess N 2 O emission from cattle feedyards, including comparison of measured and modeled emission rates, discussion of measurement methods, and evaluation of mitigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 156 publications
1
11
0
Order By: Relevance
“…Redding et al (2015) measured N 2 O‐N emissions from two Australian beef cattle feedlots, reporting mean N 2 O‐N emissions of 0.0026 and 0.27 kg ha −1 d −1 (two orders of magnitude difference). Waldrip et al (2016) reported highly variable N 2 O‐N fluxes among published studies on open‐lot beef cattle production systems. Some of this variability could be attributed to climatic and management differences among feedlots, in addition to differences in the specific method used to measure N 2 O emissions.…”
mentioning
confidence: 99%
“…Redding et al (2015) measured N 2 O‐N emissions from two Australian beef cattle feedlots, reporting mean N 2 O‐N emissions of 0.0026 and 0.27 kg ha −1 d −1 (two orders of magnitude difference). Waldrip et al (2016) reported highly variable N 2 O‐N fluxes among published studies on open‐lot beef cattle production systems. Some of this variability could be attributed to climatic and management differences among feedlots, in addition to differences in the specific method used to measure N 2 O emissions.…”
mentioning
confidence: 99%
“…In soils, monitoring changes in TN, TC, C:N ratios, NH x , and NO x may help infer N 2 O production mechanisms. However, feedyard manure is complex and heterogeneous, contains nonlimiting amounts of C and N, and has variable aerobic and anaerobic microsites (e.g., near water troughs and lounging areas, deep in the manure pack) [4,5,9,43]. As manure changes with wetting and drying, there is potential for simultaneous or coupled N 2 O production from both denitrification and nitrification [8,11,43].…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 99%
“…Beef cattle feedyards produce nitrous oxide (N 2 O) from manure [1][2][3][4][5][6]. Nitrous oxide is a potent greenhouse gas (GHG) implicated in climate change due to a global warming potential (GWP) of 265-298 carbon dioxide equivalent (CO 2 e).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations